ERYTHEMA NODOSUM IN LÖFGREN’S SYNDROME - Yu. A. Karpova; B. S. Belov; O. N. Egorova; N. M. Savushkina; S. I. Glukhova; S. G. Radenska-Lopovok (Klinicist)
Objective: to study the clinical, laboratory, and radiographic characteristics of early-stage sarcoidosis in a cohort of patients referred to a rheumatology center. Materials and methods. The investigation enrolled 125 patients (104 women and 21 men; mean age 42 ± 12 years) with the clinical and X-ray signs of Löfgren’s syndrome. All the patients were referred to a rheumatology center with diagnosed erythema nodosum (EN). The median disease duration was 1 (0.5–2.0) month. All the patients underwent comprehensive clinical examination and laboratory and instrumental studies of biochemical and immunological parameters, chest X-ray or computed tomography (CT), as well as postmortem examinations of skin and subcutaneous fat biopsy specimens were done in 15 cases. Results. EN was located on the lower leg mostly on its anterior surface (97 %), hip (35 %), upper limbs (25 %), and trunk (3 %). There was a symmetric pattern of eruptions in 50 % of the patients. Nodules fused into a conglomerate in 48 %. More than 50 % injury of the shin surface (68 %) was directly related to the number of nodules (p < 0.001; r = 0.60) and the level of C-reactive protein (p = 0.006; r = 0.38). There was a direct relationship of the number of nodules to the duration of EN (p = 0.04; r = 0.20) and their trend of fusion (p < 0.001; r = 0.39). The signs of joint injury were found in 106 (85 %) patients. The predictors of the CT frosted glass phenomenon were male sex (odds ratio (OR) 6.5; confidence interval (CI) 1.2–35.0; p = 0.026) and the presence of nodular conglomerates (OR 4.8; CI 1.4–16.1; p = 0.01). EN did not recur and articular syndrome virtually completely regressed in 90% of the patients during one-year follow-up. Conclusion. Patients with acute sarcoidosis require that physicians of different specialties, including rheumatologists, should coordinate their actions to determine the volume of further examination and to use adequate treatment.